Effect of surface modifications and using hybrid nanofluids on energy-exergy performance of regenerative evaporative cooler - Kashyap S.; Sarkar J.; Kumar A. (My University, 2025)
The regenerative evaporative cooling has emerged as efficient, cost-effective and eco-friendly technology for low and medium humid climates. The performance improvement of the regenerative evaporative cooler leads to the reduction of energy consumption in view of increasing cooling demand, which can be achieved by optimizing the design (active method) or by modifying heat transfer surfaces and working fluid properties (passive method). Hence, in this paper, the effects of using hybrid nanofluids (fluid of improved thermophysical properties) and plate surface modifications are investigated for the regenerative evaporative cooler. The comparative analysis of the four heat transferring surfaces (flat plate, capsule embossed, finned, and corrugated) is performed by numerical simulation, and the effect of the influencing variables on the performance of the heat and mass exchanger is investigated. Results show that the only use of hybrid nanofluid as a coolant in the regenerative evaporative cooler is not much fruitful, while its application with plate surface modification provides a significant amount of enhancement in terms of all considered performance parameters. The capsule embossed surface is found overally best (in terms of dew point effectiveness, coefficient of performance and exergy efficiency) among the considered plate surfaces. © 2020 Elsevier Ltd